Evaluación de vegetación urbana y temperatura superficial terrestre para la mitigación de islas de calor en el casco urbano de Santa Ana - Viteri Santos, Vinicio Orley (2025)
The present research aimed to evaluate urban vegetation and land surface temperature (LST) in mitigating heat islands in the city of Santa Ana. The research was conducted as follows: first, the state of vegetation was analyzed using the Normalized Difference Vegetation Index (NDVI) with Landsat 8 satellite images. The second objective consisted of evaluating Land Surface Temperature (LST) through conversion to top-of-atmosphere radiance, conversion to brightness temperature, vegetation fraction, and land surface emissivity. In the third objective, the intensity of the heat island was determined using NDVI and LST data. Finally, a statistical correlation was performed between NDVI and land surface temperature. The results showed variations in vegetation cover, with maximum values in 2023 (0.612) and minimum values in 2020 (-0.071). Land Surface Temperature (LST) showed higher values in 2020 (30.63°C) and lower values in 2022 (17.62°C), indicating a relationship between areas with less vegetation and higher temperatures. The correlation showed an inverse relationship between NDVI and LST (-0.64 to -0.72), demonstrating the influence of vegetation on the temperatures of the study area. Neighborhoods with higher building density, such as San Clemente, registered high Urban Heat Island effect values, while areas with tree cover, such as Caza Lagarto, showed significantly lower temperatures.